Nonoverlapping Magisteria - Gould , Stephen Jay (Filozoficzne Aspekty Genezy, 2021)
There is no conflict between science and religion. Creationism is only a local movement, prevalent only among the few sectors of American Protestantism that read the Bible as an inerrant, literally true document. Creationism based on biblical literalism makes little sense in either Catholicism or Judaism, for neither religion maintains any extensive tradition for reading the Bible as literal truth. The lack of conflict arises from a lack of overlap between the respective domains of professional expertise of science and religion. No conflict should exist because the magisteria of science and religion do not overlap. According to the principle of NOMA — “nonoverlapping magisteria” — science covers the empirical universe, while religion covers questions of moral meaning and ethical value. This principle was obeyed by both Pius XII and John Paul II. They both saw no conflict between Catholic faith and a theory of evolution. However, there is one important difference between their positions. Pius XII admitted evolution as a legitimate hypothesis, but at the same time he proclaimed that the theory of evolution had not been proven and might well be wrong. On the other hand, John Paul II stated that evolution can no longer be doubted. Now, he stated, evolution must be accepted not merely as a plausible possibility but also as an effectively proven fact. This fact is no threat to religion if one accepts the principle of NOMA. As a consequence of this principle, religion can no longer dictate the factual conclusions that belong to the magisterium of science, nor may scientists decide on moral truths.